Operational Reliability of Fire Appliances on Mercedes-Benz Chassis with Brigades of Fire Rescue Service of the Moravian-Silesian Region - Janosik, Ladislav; Cochlar, Marek; Polednak, Pavel (Communications - Scientific letters of the University of Zilina, 2015)
This paper is focused on the evaluation of data obtained from operational records of fire appliances for the period 2010 - 2013 with emphasis on fire appliances built on Mercedes-Benz chassis. These vehicles are operated by the professional units of Fire Rescue Service of the Moravian-Silesian Region. The data recorded in electronic form in operational records were analysed. The primary result of this analysis was the selection of repairs after failure. Failure severity with regard to the functional reliability of fire appliances was used as selection criterion. Subsequently the assessment of the reliability was performed by setting selected characteristics from a group of complex reliability indicators.